Interstitial pregnancies' diagnosis and management: an eleven cases series (Swiss Medical Weekly, 2013)
PRINCIPLES: Interstitial pregnancy represents 2% of ectopic pregnancies, but it is a highly morbid condition with a 2.5% of maternal mortality. Its diagnostic and therapeutic management remains controversial. The aim of this review is to describe the management of interstitial pregnancy in our institution between 2001 and 2011 and to define some general rules for the clinical practice. METHODS: Single institution retrospective study. RESULTS: Eleven women were treated for interstitial pregnancy. The median age was 33 years and the median gestity was 4. Seven patients had a history of gynaecological surgery and four interstitial pregnancies followed in vitro fertilisation. The diagnosis was made at a median gestational age of seven weeks with a median beta-HCG level of 5,838 U/l. Six of the eleven patients received an initial treatment with intracornual methotrexate, three with intramuscular methotrexate and two with surgery. The median time to beta-HCG resolution was 58 days. Three of the eleven patients needed a second line treatment: two after intramuscular methotrexate and one after intracornual methotrexate. Six patients had further pregnancies and delivered by caesarean section. CONCLUSIONS: A high prevalence of previous ectopic pregnancies, gynaecological surgery and of pregnancies resulting from in vitro fertilisation was observed. The earliness of the diagnosis was the factor that allowed a conservative treatment in most cases. Beta-HCG level follow up was fundamental in allowing a second line therapy but beta-HCG can persist over a long period of time and this must be taken into account due to its possible psychological impact. Intracornual methotrexate seems to be more efficacious than intramuscular methotrexate in our series.